Stochastic analysis of horizontal dynamic response of offshore pipe piles considering hydrodynamic pressure - Bo Yu; Libo Chen; Guang Han; Lichen Li; M. Hesham El Naggar; Wenbing Wu (Ocean Engineering, 2026)

Cryoprotective effects of fish skin collagen peptide on frozen gluten proteins: From conformational changes to functional properties - Menglei Xin; Jie Guo; Libo Wang; Sihai Han; Chonghui Yue; Zhouya Bai; Denglin Luo; Fan Zhu; Jinying Guo (Food Research International, 2026)

Divergent temporal controls of biocrusts development on soil erodibility across coverage gradients in fruit forest land - Pingzong Zhu; Wei Han; Zhenhua Pan; Lan Yang; Tao Feng; Dingbin Wang; Libo Chen; Shiqi Chen; Xiaoyan Chen (Soil and Tillage Research, 2026)

Chemo-mechanical deterioration of oolitic limestone in simulated rhizosphere environments: Differential weathering and shielding mechanisms - Yu Zhou; Naize Jia; Xiangjun Pei; Qinyuan Liang; Qiongqiong Tang; Guansheng Han; Libo Zheng (Engineering Geology, 2026)

Improvement of water redistribution, rheology and microstructure of whole black wheat dough with native inulin - Fengxia Li; Arooj Shams; Sihai Han; Zhouya Bai; Chonghui Yue; Libo Wang; Jinying Guo; Peiyan Li; Denglin Luo (Journal of Cereal Science, 2026)

Bovine milk-derived medium- and long-chain triglycerides ameliorate hepatic insulin resistance by improving mTORC2-mediated Akt activation in glucosamine-induced HepG2 cells - Yuanbin Wang; Xinyue Zang; Jiayi Zhang; Meishuai Liu; Fengmei Liao; Binyuan Han; Guofang Zhang; Peng Du; Chun Li; Libo Liu (International Dairy Journal, 2026)

Artemisinin liposomes regulates breast cancer metastasis and apoptosis through TIGIT/CD155 signal axis - Yachan Feng; Zexu Han; Jiangtao Shao; Bilgen Caliskan; Haitao Shi; Libo Du; Xiaolei Zhou; Yike Qi; Jing Zhang; Zining Hao; Xueling Guo; Jin Zhou; et al. (Apoptosis, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Modulating hydrated wheat gluten network structure with different types of polysaccharides: unraveling interaction mechanisms - Ziyu Wang; Xin Wang; Haosen Zeng; Chonghui Yue; Yuanyuan Chen; Libo Wang; Sihai Han; Peiyan Li; Zhouya Bai; Denglin Luo (Food Research International, 2026)

SF-based electro-responsive conductive composite NGCs promote peripheral nerve regeneration by inhibiting ferroptosis in Schwann cells - Guanjie Han; Tengfei Fu; Xingdong Xiang; Ping Wei; Lei Huang; Ning Wang; Mengxuan Bian; Shunyi Lu; Dihan Su; Jiayi Wang; Libo Jiang; Jian Zhang (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Thermal-mechanical coupled vibration characteristics of a rotating FGP-GNPRC stepped cylindrical shell in nonlinear thermal environment - Ziyi Wang; Hui Li; Yufeng Chang; Qingpeng Han; Ze Jian; Yu Wang; Libo Cai (Engineering Structures, 2026)

Bioinspired “dynamic interfacial priority” hydrogen-bonding network enables reprogramming of self-healing pathway - Miaomiao Li; Libo Tong; Dening Zou; Jun Cai; Xiangjun Li; Xinyu Wang; Yinxia Dong; Lixiong Han; Kuaishe Wang (Chemical Engineering Journal, 2026)

Impact of diphosphate esterification on quality characteristics of high-content inulin-enriched dough - Hui Wang; Qiang Chen; Denglin Luo; Chonghui Yue; Peiyan Li; Libo Wang; Sihai Han; Kangyi Zhang; Zhouya Bai (Journal of Cereal Science, 2025)

Chia seed oil modifies dough and gluten structure: insights into physicochemical properties and microstructure - Haosen Zeng; Sihai Han; Ziyu Wang; Tong Li; Manman Yin; Zhouya Bai; Chonghui Yue; Libo Wang; Peiyan Li; Denglin Luo (Journal of Cereal Science, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Ultrasound-assisted fermentation effectively alleviates the weakening of wheat gluten network caused by long-chain inulin and the underlying mechanism - Chonghui Yue; Yu Tang; Ziying Li; Xin Wang; Libo Wang; Denglin Luo; Peiyan Li; Sihai Han; Jinying Guo; Zhouya Bai (Food Research International, 2025)

Evaluations of two ion temperature models in IRI-2020 based on the observations from ICON and COSMIC-2 IVM - Tingwei Han; Huijun Le; Shun-Rong Zhang; Vladimir Truhlik; Natalie Reeves; Angkita Hazarika; Yujin Cho; Mei-Yu Chen; Libo Liu; Yiding Chen; Ruilong Zhang (Advances in Space Research, 2025)

An empirical model of the thermospheric winds based on ICON/MIGHTI observations - Rongjin Du; Ruilong Zhang; Libo Liu; Wendong Liu; Wenbo Li; Yuyan Yang; Han Ma; Huijun Le; Yiding Chen (Advances in Space Research, 2025)

Watt-level power density of direct borohydride fuel cells enabled by electrode local-environment and mass transport regulations - Libo Zhu; Tiantian Wu; Shuo Bi; Changchun Ke; Chang Chen; Han Tian; Fantao Kong; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Dairy products and constituents: a review of their effects on obesity and related metabolic diseases - Aili Li; Xueting Han; Libo Liu; Guofang Zhang; Peng Du; Chao Zhang; Chun Li; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2024)

Improvement of methane reforming Ni-based catalyst stability by controlling the unsaturated coordination aluminum in metakaolinite - Libo Han; Jiadong Liu; Hui Yang; Hao Qu; Ruijue Hu; Haiquan Su; Yue Su; Lili Wan (Chemical Engineering Journal, 2024)

Ultrasound-assisted process of dough for noodle production: Textural properties, moisture distribution, microstructure and cooking quality - Xingguo Li; Pengfei Liu; Zhouya Bai; Denglin Luo; Chonghui Yue; Yanhui Wu; Peiyan Li; Libo Wang; Sihai Han (Journal of Cereal Science, 2024)

Longitude structure of Martian upper atmosphere seen from MAVEN/NGIMS during 2018 Mars dust storm - Wendong Liu; Libo Liu; Zhaopeng Wu; Yiding Chen; Huijun Le; Ruilong Zhang; Wenbo Li; Han Ma; Yuyan Yang (Icarus, 2024)

The Observed Near-Surface Energy Exchange Processes over Arctic Glacier in Summer - Libo Zhou; Jinhuan Zhu; Linlin Kong; Peng Li; Shupo Ma; Fei Li; Han Zou; Meigen Zhang; Irina Repina (Journal of Meteorological Research, 2024)

A quantitative analysis of latitudinal variation of ionospheric total electron content and comparison with IRI-2020 over China - Yuyan Yang; Libo Liu; Xiukuan Zhao; Tingwei Han; M. Arslan Tariq; Yiding Chen; Hui Zhang; Huijun Le; Ruilong Zhang; Wenbo Li; Wenjie Sun; Guozhu Li (Advances in Space Research, 2024)

Light on multi-mode optical properties of carbon dots through rational surface engineering tuning strategies - Runfang Pei; Pinyi He; Fu Qin; Jianlong Ma; Cuixing Xu; Libo Qin; Wei Gao; Chun Han; Xinyu Wang; Xu Yu; Jianliang Bai; Zhijun Wang; et al. (Chemical Engineering Journal, 2024)

Busulfan-induced hepatic sinusoidal endothelial cell injury: Modulatory role of pirfenidone for therapeutic purposes - Xiangyu Ma; Jinjie Yuan; Xinyu Liu; Jiamin Xu; Jiaqi Han; Xiaoling Wang; Libo Zhao (Toxicology in Vitro, 2023)

Research on microwave hydrothermal alkaline leaching defluorination of spent cathode carbon from aluminum electrolysis - Zhangbiao Xu; Lei Xu; Zhaohui Han; Jianhua Liu; Libo Zhang; Zhi Zhu; Shifu Shen; Hang Li (Minerals Engineering, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

The East Asian wild apples, Malus baccata (L.) Borkh and Malus hupehensis (Pamp.) Rehder., are additional contributors to the genomes of cultivated European and Chinese varieties - Xilong Chen; Amandine Cornille; Na An; Libo Xing; Juanjuan Ma; Caiping Zhao; Yibin Wang; Mingyu Han; Dong Zhang (Molecular Ecology, 2023)
The domestication process in long‐lived plant perennials differs dramatically from that of annuals, with a huge amount of genetic exchange between crop and wild populations. Though apple is a major fruit crop grown worldwide, the contribution of wild apple species to the genetic makeup of the cultivated apple genome remains a topic of intense study. We used population genomics approaches to investigate the contributions of several wild apple species to European and Chinese rootstock and dessert genomes, with a focus on the extent of wild–crop gene flow. Population genetic structure inferences revealed that the East Asian wild apples, Malus baccata (L.) Borkh and M . hupehensis (Pamp.), form a single panmictic group, and that the European dessert and rootstock apples form a specific gene pool whereas the Chinese dessert and rootstock apples were a mixture of three wild gene pools, suggesting different evolutionary histories of European and Chinese apple varieties. Coalescent‐based inferences and gene flow estimates indicated that M . baccata – M . hupehensis contributed to the genome of both European and Chinese cultivated apples through wild‐to‐crop introgressions, and not as an initial contributor as previously supposed. We also confirmed the contribution through wild‐to‐crop introgressions of Malus sylvestris Mill. to the cultivated apple genome. Apple tree domestication is therefore one example in woody perennials that involved gene flow from several wild species from multiple geographical areas. This study provides an example of a complex protracted process of domestication in long‐lived plant perennials, and is a starting point for apple breeding programmes.

Effects of dietary mannan oligosaccharides on growth, non-specific immunity, and intestinal health in juveniles of the Japanese sea cucumber (Apostichopus japonicus) - Xin Gao; Haojie Zhai; Libo Wei; Lidong Shi; Lin Yan; Zuxiang Peng; Wei Wang; Tongjun Ren; Yuzhe Han (Aquaculture International, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Sandwich-structured nickel/kaolinite catalyst with boosted stability for dry reforming of methane with carbon dioxide - Hao Qu; Hui Yang; Libo Han; Sihui He; Jiadong Liu; Ruijue Hu; Haiquan Su; Yue Su (Chemical Engineering Journal, 2023)

Surface heat transfer changes over Arctic land and sea connected to Arctic warming - Linlin Kong; Han Zou; Libo Zhou; Jinhuan Zhu (International Journal of Climatology, 2022)
Turbulent heat transfer from surface to atmosphere is important in the atmospheric energy balance over the Arctic, thereby impacting the remarkable warming that occurs in this region. The impact of heat transfer over the Arctic land and sea (approximate Arctic Ocean) on Arctic warming could be distinct, owing to different heat sources and physical processes on the interfaces. This study sought to analyse the heat transfer and changes over the Arctic land and sea and their contributions to those over the entire Arctic, and discuss the connection between the heat transfer changes and Arctic warming based on ERA5 reanalysis. The Arctic surface releases heat to the atmosphere, with an annual average of 4.5 × 10 14 W, which is mainly contributed by the Arctic land in summer and sea in winter. From 1979 to 2018, the amount of heat release was found to markedly increase, with an annual trend of 0.94 ± 0.31 W/(m 2 decade). A faster increase occurred in summer and was contributed by both the Arctic land and sea. In contrast, a slower increase occurred in winter and was only contributed by the sea. The heat transfer changed heterogeneously over the Arctic land and sea, with three major changes: Northern Russia Increase over northern Russia in summer, Northern Barents Increase over the northern Barents Sea in winter, and Nordic Sea Decrease over the Nordic Sea and northern Greenland Sea in winter. Notably, the heat transfer change over the Arctic land and sea could be connected to Arctic warming, especially the three major changes, based on distinct feedback processes, which could impact future Arctic warming. Overall, the Arctic land and sea play distinct roles in the heat transfer change and connection to Arctic warming, with the land being more important in summer and the sea being more important in winter.

Atmospheric energy change in the Arctic troposphere under Arctic warming - Linlin Kong; Han Zou; Libo Zhou; Jinhuan Zhu (International Journal of Climatology, 2022)
The atmospheric energy is an essential property of atmosphere, mainly composed of internal, potential and latent energies, and could be changed by energy balance processes. The recent Arctic warming and wetting could have direct impacts on the internal and latent energies, and indirect impacts on energy transport and transformation. It is necessary to understand if and how the Arctic atmosphere, described by energy, has been changed under Arctic warming. This study attempts to analyse and discuss the changes of tropospheric energy over the Arctic (north of 66°N) from 1979 to 2018, including the general status, seasonal variation, long‐term trend, interannual variability and extremes. Three latest reanalysis products, ERA5, CFSR and JRA55, are used in this study, with acceptable reliability in validation with radiosonde observations. The reanalysis products exhibit high consistence in energy changes over the Arctic. The main results are obtained as (a) the Arctic troposphere has a total energy of 3.42 × 10 22 J, dominated by internal energy; (b) an increase of total energy in the Arctic troposphere is found on annual basis, with a trend of 7.20 ± 5.47 × 10 19 J·decade −1 , and possibly enhanced in last 20 years, mainly contributed by internal energy; (c) the tropospheric energy over the Arctic had a interannual variability of 1.95 × 10 20 J, mainly supported by internal and potential energies, and the extremes of high energies were gradually enhanced. Therefore, the Arctic atmosphere, described by energy, has been changed under Arctic warming, evidenced by significant increases of total energy and its components in the Arctic troposphere on annual basis.

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Atmospheric Structure Observed over the Antarctic Plateau and Its Response to a Prominent Blocking High Event - Jinhuan Zhu; Libo Zhou; Han Zou; Peng Li; Fei Li; Shupo Ma; Linlin Kong (Journal of Meteorological Research, 2021)

Transcription profiles reveal the regulatory mechanisms of spur bud changes and flower induction in response to shoot bending in apple (Malus domestica Borkh.) - Libo Xing; Dong Zhang; Siyan Qi; Xilong Chen; Na An; Youmei Li; Caiping Zhao; Mingyu Han; Juan Zhao (Plant Molecular Biology, 2019)

The Myosin5‐mediated actomyosin motility system is required for Verticillium pathogenesis of cotton - Zhidi Feng; Juan Tian; Libo Han; Yuan Geng; Jie Sun; Zhaosheng Kong (Environmental Microbiology, 2018)
Summary The vascular wilt fungus Verticillium dahliae is one of the most destructive pathogens of cotton ( Gossypium hirsutum ) and many other economically important dicot plants. Fungal pathogens require Myosin‐mediated actomyosin motility system for colonization of their host plants; however, the mechanisms underlying this process have not been fully characterized for V. dahliae . Here, in a knock‐out experiment, we characterized the role of VdMyo5 , a member of the Myosin V family, before and during infection of cotton and Arabidopsis thaliana . The VdMyo5 deletion mutant (ΔVdmyo5 ) fungi showed obvious defects in the development of conidia and the polarized elongation of vegetative hyphae, but no inhibition of host root penetration. Overall, the ΔVdmyo5 fungi exhibited dramatically reduced virulence in cotton and Arabidopsis , with almost no colonization in sections of host vascular tissue. We found labelled Myosin5‐GFP to be specifically enriched at the hyphal tip, co‐localized with FM4‐64 labelled Spitzenkörper, which is the vesicle supply centre in filamentous fungi. Comparative secretome analysis revealed that proteins associated with cell wall modification and degradation of reactive oxygen species were significantly altered in mutant strains. Our results indicate that Myosin5 is required for vegetative growth and full virulence, possibly by regulating vesicle transport. The findings provide important insight into the cellular mechanisms of Verticillium pathogenesis.

Overexpression of GhPFN2 enhances protection against Verticillium dahliae invasion in cotton - Wenyan Wang; Yongduo Sun; Libo Han; Lei Su; Guixian Xia; Haiyun Wang (Science China Life Sciences, 2017)

Phylogenetic analysis of IDD gene family and characterization of its expression in response to flower induction in Malus - Sheng Fan; Dong Zhang; Libo Xing; Siyan Qi; Lisha Du; Haiqin Wu; Hongxia Shao; Youmei Li; Juanjuan Ma; Mingyu Han (Molecular Genetics and Genomics, 2017)

CMDH4 encodes a protein that is required for lead tolerance in Arabidopsis - Libo Yang; Tingting Fan; Lingxia Guan; Yongbing Ren; Yi Han; Quoqing Liu; Yongsheng Liu; Shuqing Cao (Plant and Soil, 2017)

Vertical structures of atmospheric properties in Southeast Tibet during the South Asian summer monsoon in 2013 - Libo Zhou; Fei Li; Jinhuan Zhu; Han Zou; Shupo Ma; Peng Li (Journal of Meteorological Research, 2016)

The two domains of cotton WLIM1a protein are functionally divergent - Libo Han; Yuanbao Li; Yongduo Sun; Haiyun Wang; Zhaosheng Kong; Guixian Xia (Science China Life Sciences, 2016)

Cross-correlation Coefficients for the Study of Repeating Earthquakes: An Investigation of Two Empirical Assumptions/Conventions in Seismological Interpretation Practice - Libo Han; Zhongliang Wu; Yutong Li; Changsheng Jiang (Pure and Applied Geophysics, 2014)

Characteristics of the Upper Jurassic marine source rocks and prediction of favorable source rock kitchens in the Qiangtang Basin, Tibet - Libo Wang; Yeqian Zhang; Junjie Cai; Guangzhi Han (Journal of Earth Science, 2013)

The role of snow/ice cover in the formation of a local Himalayan circulation - Shupo Ma; Libo Zhou; Han Zou; Meigen Zhang; Peng Li (Meteorology and Atmospheric Physics, 2013)

The local atmosphere and the turbulent heat transfer in the Eastern Himalayas - Han Zou; Peng Li; Shupo Ma; Libo Zhou; Jinhuan Zhu (Advances in Atmospheric Sciences, 2012)

Variation of NDRG2 and c-Myc expression in rat heart during the acute stage of ischemia/reperfusion injury - Zhongchan Sun; Lan Shen; Xiang Sun; Guang Tong; Dongdong Sun; Tenglong Han; Guodong Yang; Jian Zhang; Feng Cao; Libo Yao; Haichang Wang (Histochemistry and Cell Biology, 2011)

Vertical air mass exchange driven by the local circulation on the northern slope of Mount Everest - Libo Zhou; Han Zou; Shupo Ma; Peng Li; Jinhuan Zhu; Cuiping Huo (Advances in Atmospheric Sciences, 2011)

Middle-high latitude N2O distributions related to the Arctic vortex breakup - Libo Zhou; Han Zou; Yougqi Gao (Advances in Atmospheric Sciences, 2006)

An observational study on the vertical distribution and synoptic variation of ozone in the arctic - Zou Han; Zhou Libo; Jian Yongxiao; Liu Yu (Advances in Atmospheric Sciences, 2002)

The Scandinavia ozone loss and surface heating - Zhou Libo; Zou Han; Ji Chongping; Wang Wei; Jian Yongxiao (Advances in Atmospheric Sciences, 2001)

ENSO signal in total ozone over Tibet - Zou Han; Ji Chongping; Zhou Libo; Wang Wei; Jian Yongxiao (Advances in Atmospheric Sciences, 2001)

QBO Signal in total ozone over Tibet - Zou Han; Ji Chongping; Zhou Libo (Advances in Atmospheric Sciences, 2000)